2020
DOI: 10.1021/acsabm.0c00871
|View full text |Cite
|
Sign up to set email alerts
|

Thin TiO2 Coatings by ALD Enhance the Cell Growth on TiO2 Nanotubular and Flat Substrates

Abstract: The present work exploits Ti sheets and TiO 2 nanotube (TNT) layers and their surface modifications for the proliferation of different cells. Ti sheets with a native oxide layer, Ti sheets with a crystalline thermal oxide layer, and two kinds of TNT layers (prepared via electrochemical anodization) with a defined inner diameter of 12 and 15 nm were used as substrates. A part of the Ti sheets and the TNT layers was additionally coated by thin TiO 2 coatings using atomic layer deposition (ALD). An increase in ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Conformal titanium oxide nanocoatings, silver NPs, and structures combining coatings and NPs have been successfully prepared by ALD. According to a number of in vitro and in vivo studies, it is known that ALD titanium oxide films have a positive effect on the proliferation, differentiation and osseointegration of titanium implants [ 19 , 30 , 31 ]. According to our results, as-deposited ALD TiO 2 coatings have a less hydrophilic surface than polished titanium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conformal titanium oxide nanocoatings, silver NPs, and structures combining coatings and NPs have been successfully prepared by ALD. According to a number of in vitro and in vivo studies, it is known that ALD titanium oxide films have a positive effect on the proliferation, differentiation and osseointegration of titanium implants [ 19 , 30 , 31 ]. According to our results, as-deposited ALD TiO 2 coatings have a less hydrophilic surface than polished titanium.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, ALD was used to obtain such structures, but only for the production of one of the materials. In most cases, titanium oxide [ 30 , 31 , 43 ] was deposited, but there are also studies on silver NPs deposited on nanotubes of various sizes [ 34 ]. In this respect, the approach proposed in our work is unique, because it uses only ALD to produce complex multicomponent material.…”
Section: Discussionmentioning
confidence: 99%
“…Perumal et al showed the corrosion resistance of ATO nanotubes were improved by polyaniline polymer [ 48 ] but the pores of nanotubes were partially filled or disappeared after deposition of the polymer. Motola et al deposited thin titanium dioxide coating on ATO nanotubes using atomic layer deposition to enhance cell growth [ 49 ]. The coating was deposited on nanotubes with 0.3 nm thickness successfully.…”
Section: Discussionmentioning
confidence: 99%
“…TiO 2 has been diversely employed in solar devices in the form of cathodes, light scatterers, electron collectors, high wavelength transmitters, etc. These applications are possible due to its tunable conductivity, resistance to weathering, self-cleaning ability, excellent transmittance of solar radiation, and ease of fabrication [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. TiO 2 has been utilized in the form of a mesoporous nanostructure to increase scattering, which increases the interaction of light with absorbing materials and eventually improves the absorption efficiency [ 31 ].…”
Section: Introductionmentioning
confidence: 99%